Tingkat Kelayakan Bahan Ajar Fisika Berbasis Media Sosial Edmodo sebagai Sumber Belajar Interaktif - Aristantia, Nia; Jamaluddin, Wan (Universitas Islam Negeri Raden Intan Lampung, 2018)
Abstrak: This study aims to determine how the feasibility level of physics-based materials edmodo social media as an interactive learning resource. The steps of research are based on Research and Development / R and D by Sugiyono. This research was conducted until the seventh stage of development stage. The subjects of this study were students of SMAN 3 Kotabumi, SMAN 1 Kotabumi, and SMA N 13 Bandar Lampung. Data collection techniques in this study using a questionnaire. The data collected were analyzed using quantitative and qualitative descriptive statistics. The resulting product is categorized as